Chinese College Students’ Career Education Skills and Career Adaptability: The Mediating Effect of Career Decision-Making Self-Efficacy - Liu, Huini; Paramalingam, Muhantha (Journal of Neonatal Surgery, 2025)
Objectives: The post-epidemic period has increased the uncertainty surrounding college students' employment and job search. As a result, it is essential to assist students in making career decisions in an unpredictable setting. Due to the increasing ambiguity around their future intentions, university students getting ready to enter the profession may feel more stressed and anxious. Their professional progress may be impacted by controlling such negative feelings and adapting to the changing environment. In the past, job searchers have faced significant obstacles due to the change in employment patterns and the extraordinary disruptions brought on by incidents like COVID-19. This is especially true for college students getting ready to start working. In this regard, improving career flexibility is essential to directing their professional growth. Method: In this research, 273 Chinese undergraduate students were asked to examine the relationship between professional education skills and job flexibility. The study also aimed to ascertain how this connection was impacted by professional decision-making self-efficacy. Results: Career education skills and work flexibility have a substantial positive link, according to the correlation study's findings. Moreover, the results of the mediation model showed that career education skills significantly increase career adaptability in addition to the mediating function of college students' self-efficacy in professional decision-making. When creating and expanding career education programs, institutions should prioritise them, according to this analysis. Conclusion: College students should be assisted in creating a flexible and positive career perspective in addition to helping them identify particular career goals. This will enable them to more readily adapt to any changes that may arise along their professional adventures.